Girls' literacy experiences in and out of school : learning and composing gendered identities - O'Quinn, Elaine. (Routledge, 2013)
"Through thoughtful analysis of girls' historical literacy experiences, their contemporary reading and writing lives, and trends in young adult literature, this book sheds new light on how teachers can better understand and create classroom experiences that make girls visible both to themselves and to others.Historically, the status of girls has evoked much less research than that of boys. Recently emerging scholastic and strategic study concerning the vulnerability of girls is adding a vital missing component to this continually emerging discourse. Looking at many aspects of girls' gendered lives, this text considers the specific perspectives of the social and cultural constructions that script gender, particularly as applies to girls in our classrooms. Prominent scholars in their respective fields examine the myriad forces that shape the lives of American girls, from the earliest didactic records of manuals and books of conduct to current artifacts of contemporary culture. By investigating both the scholarly literature on girls as well as well as the primary sources of a material culture, the authors seek to unravel how adolescent girls learn and seek to compose identities. By closely examining girls' practices, in which are embedded issues of class, race, ethnicity, immigrant status, and sexuality, the text considers some of the values, structures, and trajectories that have come to define teenage girlhood. Its distinctive contribution is to unpack some of the assumptions of girls in English classrooms and to critically examine their experiences as they try to fit preconceived norms while forming their own personhood"-- Provided by publisher.